Influencing Factors of Social Anxiety of Undergraduate Nursing Students Based on Random Forest Model: A Cross‐Sectional Study - Yuling Jia; Yuexue Yue (Nursing Open)
ABSTRACT Aim Social anxiety is common among students, yet research specifically on undergraduate nursing students is scarce. Previous studies have identified various influencing factors but lack a clear ranking of their importance, making it challenging to implement effective intervention strategies with limited resources. This study aims to assess the level of social anxiety in undergraduate nursing students and rank the importance of its influencing factors, providing essential insights for developing efficient and targeted interventions. Design A cross‐sectional study was conducted with 546 undergraduate nursing students in China. Methods Data were collected via a web‐based questionnaire, which included the fear of positive and negative evaluation scale, the self‐efficacy scale, and the social anxiety scale. The random forest model was employed to analyse the data and rank the importance of the influencing factors. Results The total social anxiety score among undergraduate nursing students was 11.20 ± 4.71. Social anxiety had a positive correlation with both fear of positive evaluation (r = 0.521, p < 0.001) and fear of negative evaluation (r = 0.648, p < 0.001) and a negative correlation with self‐efficacy (r = −0.273, p < 0.001). According to the random forest model, the top five predictors of social anxiety in this study were fear of negative evaluation, fear of positive evaluation, personality traits, self‐efficacy, and academic performance. Conclusion Attention to social anxiety in undergraduate nursing students is necessary, particularly for those with a higher fear of evaluations, introverted personalities, lower self‐efficacy, and poor academic performance. Nursing educators should consider recognising social anxiety and developing personalised interventions tailored to the specific characteristics of these students. Patient or Public Contribution All participants contributed to the conducting of this study by completing self‐reported questionnaires.